In‐Depth Analysis of Electrochemical Reaction Rate Distribution in Microfluidic Fuel Cell with Flow‐Through Electrodes. Issue 1 (16th November 2022) - Li, Li; Ling, Lei; Shan, Shuai; Xie, Yajun; Zhang, Lanchun; Han, Bingyuan; Bei, Shaoyi; Zheng, Keqing; Xu, Qiang
Abstract : Nonuniform reaction rate distributions are commonly observed in the microfluidic fuel cell (MFC) systems, which bring a significant limit to the cell output. Herein, systematic analyses are performed to explore the electrochemical reaction rate distributions in the flow‐through electrodes of MFCs, and in‐depth understanding of the distribution mechanisms under various operating conditions is presented via a MFC performance simulation model. The results demonstrate that the high‐reaction‐rate regions locate at the inner parts of the flow‐through electrodes in the high flow rate and high‐reactant concentration cases which are ohmic‐resistance dominated, while moving toward the outer parts of the electrodes with the decreasing of flow rate and/or reactant concentration due to the increased concentration‐related activation resistance. A series of performance enhancement strategies are also proposed and examined. It is found that smaller electrode aspect ratio, reduced electrode distance, excess supporting electrolyte, and larger specific surface area are desirable in the high flow rate and high‐reactant concentration cases, which can boost the cell performances significantly. This work can contribute to the optimal designs of microfluidic fuel cells under various application scenarios in the future. Abstract : Herein, systematic analyses of the reaction rate distributions under various operating conditions are performed, in‐depth understandings of the reaction rate distribution mechanisms are presented, and based on the results, a series of performance enhancement strategies is proposed and examined for the future design of microfluidic fuel cells under various application phenomena.